Diseño e implementación de un sistema de simulación de sonidos cardiacos, pulmonares e intestinales en un maniquí controlado con una aplicación interactiva educativa para los estudiantes de salud. - Hidalgo LLano, Segundo Manolo (2025)
In today's academic environment, medical simulators are an invaluable tool for both students and instructors. These devices allow practicing procedures in a realistic way, which would be almost impossible to perform on cadavers or patients, due to the risk it would represent for both the patient and the health personnel. In this degree project, an electronic simulation system of cardiac, pulmonary and intestinal sounds is being developed in a mannequin controlled through an interactive application. This application is user-friendly and easy to use, which allows programming, controlling and reproducing the aforementioned sounds. This aims to facilitate the auscultation learning process for students, while allowing them to understand the correlation between these sounds and the anatomy of the human body. This system is especially useful in the training of future physicians, as it provides them with a comprehensive perception of their actions, especially in complex and interprofessional healthcare situations. With conventional auscultation, students can identify various organs, such as the heart (which functions as a pump that sends and receives blood through arteries and veins, generating sounds in different areas of cardiac auscultation). In addition, it allows the diagnosis of respiratory diseases and auscultation of the stomach, where the intestines, being hollow cavities, produce noises known as borborygmi. These sounds are normal, but other sounds may indicate problems such as hyperactivity, obstructions or blockages. Keywords: Sound Simulator, Electronic System, Auscultation Manikin, Auscultation Manikin